UTILIZATION OF MADURA COARSE AND FINE AGGREGATES IN LOW-TRAFFIC ROAD PAVEMENTS - Ratih Sekartadji; Kurnia Hadi Putra; Theresia Maria Candra Agusdini; Mutiara Firdausi; Ita Suhermin Ingsih; Faizal Maulana (Journal Innovation of Civil Engineering (JICE), 2023)
Aggregates from Sampang are still rarely used in flexible pavement. Therefore, this research is to identify the effects of coarse aggregate and soft aggregate from Sampang – Madura, to recognize their performance in the HRS – WC mixture. It adopted Bina Marga General Standards 2010, Division 6 (Revision 3) for HRS – WC mixture, by testing the physical characteristic of coarse aggregate and soft aggregate from Sampang (in terms of specific gravity and absorption, coarse aggregate wear and tear, and sieve passing Nr. 200) and Marshall Characteristic Testing with asphalt content variables of 6%, 6,5%, 7%, 7,5%, and 8% of the total mixture, each with 3 tested objects. With reference to the physical aggregate characteristic, it was found that the coarse aggregate satisfied the specification standard. On the other hand, the value of the specific gravity of the soft aggregate was still lower than the specification standard, i.e., 2,25 gram/cm2, while the minimum standard was 2,5 gram/cm3. It definitely affected the performance of the HRS – WC mixture. As the volume of the mixture was larger and left a larger cavity in the mixture, it required larger content of asphalt in order to generate a mixture qualifying the Bina Marga General Standards 2010, Division 6 (Revision 3). Based on the results of Marshall Test Characteristic Testing, it was found that the optimum content of asphalt was 8% of the total mixture. Keywords: Sampang; Coarse aggregate and soft aggregate; HRS WC; Aggregates physical characteristic, Marshall Testing